LUIS TOUR RPG: Explore, discover, watch documentaries, animation and complete quests - Maulidya Nur Aini; Salsabila Firdausi Nuzula; Risa Septyana; Fatiya Rosyida; Yuswanti Ariani Wirahayu; Budi Handoyo (Research and Development in Education (RaDEn), 2024)
In social studies learning, the challenges faced are not only related to real-life problems such as the environment and society, but also the demands to develop high-level thinking skills, such as critical, reflective, and creative. This study aims to develop RPG game learning media based on differentiated learning by combining animated videos and documentary videos in the media. This study uses the ADDIE development model. The development research was carried out at SMP Negeri 24 Malang. After that, the LUIS TOUR media was refined and then tested again with a trial on 24 grade VIII students. The validity and practicality tests of this method were carried out in the context of social studies learning, with the results showing an increase in aspects of independence, cooperation, critical thinking skills, and student questioning skills. The results of expert validation and readability tests show that the LUIS TOUR media is very feasible. In addition to the validation results, a practicality test was also carried out by students with a score of 86% each. This study contributes to the integration of technology in 21st century learning, especially in developing learning media that are relevant to the challenges of the 5.0 society era.